Large B-cell lymphoma with IRF4 rearrangement: a special tonsillar lymphoma in children - Jie Man; Yizhen Wang; Xiaowen Zhai; Lian Chen; Yangyang Ma; Hongsheng Wang (Elsevier, 2019)
Objective: To identify the clinicopathological features and prognosis of large B-cell lymphoma(LBCL) with interferon regulation factor 4 (IRF4) rearrangement. Methods: We retrospectively analyzed the medical records of four patients from Children's Hospital of Fudan University diagnosed with LBCL with IRF4 rearrangement during Sep. 2014 to Oct. 2018, and performed a literature review. Results: Four patients had an average age of 5.7 years. The median duration from presentation to final diagnosis was 25.7 days. All 4 patients were admitted to the hospital due to severe snoring with no causes. The patients showed enlarged lymph nodes in the neck without tenderness. All 4 cases presented as localized disease (St-jude stage II). Lactate dehydrogenase (LDH) and serum albumin were all in the normal range. Morphology showed that normal lymphoid follicles were diffusely invaded by consistent, medium-sized large cells with obvious nucleoli. CD20, CD79α, PAX5, CD10 and BCL6 were diffusely positive. Neoplastic cells were also strongly positive for MUM1 and Ki-67. IRF4 gene rearrangement was detected as positive by IRF4 dual-color break-apart probe. Four patients underwent routine chemotherapy post bilateral tonsillectomy operation. Three achieved complete remission (CR) while the newly diagnosed one is during the second course of chemotherapy. Conclusions: Tonsillar LBCL with IRF4 rearrangement in children presents distinct clinicopathologic and molecular genetic features, and it usually has a favorable outcome. Keywords: Large B-cell lymphoma, IRF4 rearrangement, Child, Tonsil, Prognosis